Communication Strategy For Women Organizations In Minimizing Female Violence During Pandemic - Dzikrina Asqha Mahardika (INJECT (Interdisciplinary Journal of Communication), 2020)
The emergence of pandemic Covid-19 which struck many countries reveals a veil from the viewpoint of the women's world. Besides women are easily infected with Covid-19, apparently women are also prone to violence because of their pandemic. This research used qualitative descriptive research. The research concentrate on communication strategies and used Ledinghem Burning's theory of Relationship Management Theory. The research also took samples of women's organizations that concentrate on dealing with cases of violence against women who are Legal Resource Center for Justice Gender and Human Rights (LRC-KJHAM) Central Java province. Researchers were looking for data from primary and secondary sources. Data collection techniques of this study were interview techniques and documentation. The results of this research was to know the strategy of communication implemented by LRJ-KJHAM in minimizing the occurrence of women violence in the pandemic is known as the Central Java region. The research also shows that the Relationship Management Theory was applied by the LRC-KJHAM manager so that the women remain protected from violence despite the health protocol when the Covid-19 runs strictly.